THE EFFECT OF LEADER-MEMBER EXCHANGE, MANAGERIAL SUPPORT, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH THE MEDIATION OF WORK MOTIVATION IN THE MILLENNIAL GENERATION AND GENERATION Z AT PT PABRIK KERTAS TJIWI KIMIA TBK - Dara Anindya Putri Umagapi; Budi Eko Soetjipto; Sopiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research is motivated by the performance dynamics of Millennial and Generation Z employees in the paper production division of PT Pabrik Kertas Tjiwi Kimia Tbk. As younger employees tend to value supportive communication, organizational attention, and a comfortable work environment, it becomes important to understand how Leader–Member Exchange (LMX), managerial support, and the work environment influence their motivation and performance. This study examines the effects of these variables on employee performance, with work motivation positioned as a mediating factor. Leader–Member Exchange (LMX) reflects the quality of reciprocal interactions between supervisors and employees. Managerial support is viewed through the lens of Perceived Organizational Support (POS), which highlights employees' perceptions of how much the organization and supervisors value and support them. The work environment is analyzed based on ergonomic and industrial psychology perspectives, emphasizing physical comfort, safety, and psychological conditions. Work motivation is grounded in Self-Determination Theory (SDT), which explains how the fulfillment of autonomy, competence, and relatedness drives individuals to perform optimally. A quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed. The study involved a population of 466 Millennial and Gen Z employees in the production division, from which 218 respondents were selected through simple random sampling. Data were collected using a Likert-scale questionnaire and tested for validity and reliability through convergent validity, discriminant validity, composite reliability, and Cronbach's Alpha. Hypotheses were evaluated through outer and inner model assessments and bootstrapping procedures. The findings reveal that LMX and managerial support do not have a significant direct effect on employee performance. However, both variables show a significant positive influence on work motivation. The work environment significantly influences both motivation and performance. Work motivation itself significantly contributes to performance and mediates the relationship between the independent variables and performance. These results indicate that for Millennial and Gen Z employees, motivation plays a crucial role in translating workplace relationships, managerial support, and environmental conditions into improved performance. Theoretically, this research reinforces the relevance of Leader–Member Exchange Theory, Perceived Organizational Support Theory, ergonomic and industrial psychology concepts, and Self-Determination Theory in understanding younger employees in manufacturing settings. Practically, the study suggests that companies should enhance employee performance by strengthening supervisor–employee relationships, improving organizational support, and optimizing ergonomically sound and psychologically supportive work environments.